Rebirth Epistemological Paradigm as a transformational tool for individuals and organizations post COVID-19 outbreak: a new normal adaptation model - Sekgapane, Del; Costa, King (My University, 2020)
COVID-19 has impacted how organisations function the world over. Adaptation models that will bring sustainability in the new normal will need to integrate humanistic perspectives beyond the five normal dimensions of emotional intelligence to inculcating the cultural perspectives and indegenous methods of community engagement and inquiry. This article is one of a series produced by authors, pursuant to an intense doctoral study by one of the authors which culminated in a Rebirth model. The setting of the study was at one of the largest banking groups in South Africa, whereby collective engagement for Organisational Change and Development (OCD) using multiple methods within the intepretivist ontological phylosophy was investigated. The study resulted in the establishment of Rebirth first as a paradigm for enquiry, complemented by phenomenological research strategy in conjuction with the Integral Research Approach (IRA) using both Feminist Transformative theories in a Participatory Action Research (PAR) mode for data collection. This paper provides basic steps into undertanding Rebirth philosophy through explication of its six (6) pillars, namely; Ubuntu-Botho, Nature, Dialogue, Story-telling, Symbols and Tribal Circle. Core to the Rebirth philosophy are the eight (8) human factors of behavior, classified as quotients in a spiral direction representing the womb as a place of seed germination to birth and ultimate attainment of knoledge that leads to productive execution.
Keywords: Behavior; Change management; Epistemologies; Organisational Development; Research; Transformation